DEVELOPMENT STRATEGY OF COCOA AGROINDUSTRY BASED ON FARMER GROUPS IN KAPANEWON PATUK GUNUNGKIDUL REGENCY DAERAH ISTIMEWA YOGYAKARTA - Dyah Indriyaningsih Septeri (Jurnal Agroindustri, 2022)
Cocoa is one of the leading commodities in the plantation sector in Gunungkidul Regency. The purpose of this study was to describe the cocoa agroindustry development system in Kapanewon Patuk, Gunungkidul Regency, D.I Yogyakarta, precisely in Nglanggeran Village; and analyze the agro-industry development strategy based on farmer groups. The research method used in this study is a qualitative method with a descriptive approach, with data collection techniques using observations, interviews and literature studies. This study begins by analyzing the characteristics of cocoa farmer groups, cocoa agroindustry in Kapanewon Patuk. Then proceed with determining the cocoa agroindustry development strategy based on farmer groups through SWOT analysis. The results showed that the cocoa agro-industry in Kapanewon Patuk has been implemented on a home-industrial and industrial scale. Cocoa farmer groups as providers of raw materials have been able to process cocoa beans (fermented) into processed raw materials such as chocolate-based foods and beverages. In addition to the role of farmer groups, local government support, DIY BPTP, LIPI BPTBA, and Bank Indonesia were able to develop cocoa agroindustry in Kapanewon Patuk. Cocoa agro-industry development strategies can develop after formulating several required subsystems, including raw material subsystems, operational subsystems (production processes), marketing subsystems, and supporting subsystems.